Impact of Integrating Science and Engineering Teaching Approach on Students Achievement: A Meta Analysis (Jurnal Pendidikan IPA Indonesia, 2021)
STEM teaching approach has attracted the attention of science educators as a panacea in addressing the deteriorating interest in STEM learning. However, the impact of STEM teaching approach on students’ achievement is scarcely discussed. Thus, this study aimed to explore the impact of integrating Science and Engineering teaching approach on the achievement of students. This meta-analysis was conducted systematically on articles published between January 2000 to January 2020 which were retrieved from five databases (EBSCOhost, Emerald, Scopus, Web of Science and ERIC).  Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were applied to ensure a rigorous selection of the desired research articles. The data were then assessed using two online statistical effect size calculators. A total of 14 effect sizes were calculated. The overall mean effect size obtained was of high effect (es=2.61).  The Engineering Design Process (EDP)(es=3.26, high effect) was the most effective teaching approach in enhancing students’ understanding, as opposed to design-based learning.   An implication of the study is that EDP should be the basis for other teaching approaches in SE. Solving and creating tasks encourage application of concepts that then lead to enhancement of achievement.